Follicle-stimulating hormone stimulates estradiol-17beta synthesis in cultured Sertoli cells. - Dorrington, J H (1975)
Sertoli cells isolated from testes of 20-day-old rats and maintained in primary culture synthesized estradiol-17beta [1,3,5(10)-estratriene-3,17beta-diol] (measured by specific radioimmunoassay) when testosterone (17beta-hydroxy-4-androsten-3-one) 0.5 muM, was added to the culture medium. No detectable estradiol synthesis occurred when cells were incubated in medium containing pregnenolone (3beta-hydroxypregn-5-en-20-one), 0.5 muM, or containing no added steroid substrate. Follicle-stimulating hormone (FSH) (NIH-FSH-S10, 5 mug/ml) stimulated estradiol synthesis 12- to 80-fold when added to medium containing testosterone, but not when added to medium containing pregnenolone or no exogenous steroid substrate. A highly purified FSH preparation, with FSH potency 50 times that of the NIH-FSH, caused a similar stimulation at a concentration of 0.25 mug/ml of medium, whereas luteinizing hormone (NIH-LH-S18, 5 MUG/ML) Caused only marginal stimulation. Dibutyryl-adenosine 3':5' cyclic monophosphate, 0.1 mM, caused a 30-fold increase in estradiol synthesis by Sertoli cells cultured in medium containing testosterone. These studies provide direct demonstration of estradiol-17beta production by Seroli cells from normal animals, and offer evidence that the synthesis of this steroid is regulated at the level of the aromatizing enzyme system by FSH and adenosine 3':5' cyclic monophosphate.